Answer: y= 3x + 8
Explanation:
First find the slope of the line between (0,8) and (-2,2) using m= y2-y1/x2-x1, which is the change of y over the change of x.
It would be 2-(8)/-2-(0)
Next multiply 1 . 8, then subtract 8 from 2.
= 2-8/ -2 -(0)
= -6/-2-(0)
Next, multiply -1 . 0
= -6/-2+0
Add -2 and 0
= -6/-2
Divide -6 by -2
m= 3
Next, use the slope 3 and our last given point (0,8) to substitute for x1 and y1 in the point-slope form y-y1 = m(x-x1).
y-(8) = 3. (x-(0))
Next, simplify the equation and keep it in point-slope form
y-8 = 3. (x+0)
Then solve for y
add x and 0
y-8= 3x
add 8 to both sides of the equation
y= 3x + 8